Priogymnanthus saxicolus (Oleaceae), a new species from Minas Gerais, Brazil - Lombardi, Julio Antonio (Phytotaxa, 2015)
Priogymnanthus saxicolus Lombardi, a new species of Oleaceae, is described and illustrated. It is distinguished by the unique combination of persistently villose abaxial leaf surface, short congested inflorescences, and nearly sessile flowers, which do not match the characteristics of the other two species of Priogymnanthus.